Experiences of Family Belonging among Two Generations of Sexually Diverse Australians. Issue 2 (19th November 2019) - Newman, Christy E.; Persson, Asha; Prankumar, Sujith; Lea, Toby; Aggleton, Peter
Abstract : Objective: To extend knowledge about how lesbian, gay, bisexual, trans+, and queer (LGBTQ+) people relate to their families of origin by paying particular attention to their experiences of belonging within this context. Background: Although the impact of family rejection on young LGBTQ+ people is well established, circumstances and expressions of family belonging are less well understood. Method: Taking a qualitative, social generational approach, we asked two groups of Australians, born in the 1970s ( n = 14) and 1990s ( n = 18), about their experiences of family relationships when they were growing up sexually and/or gender diverse. Results: A subset of participants described feeling accepted by families of origin, although very few were gender diverse. The 1970s cohort described these experiences as culturally exceptional, and the 1990s cohort as a birthright . Examples from both demonstrate how family belonging can remain conditional . Conclusion: Experiences of family belonging reveal both the importance of family to the well‐being and flourishing of LGBTQ+ people, and the entanglement between individual and social understandings of what family acceptance comprises. Implications: Scholars and support service providers may benefit from recognizing that some sexual minorities experience belonging in their families of origin, but work remains in understanding and challenging the conditions that some families continue to impose.